Biomass gasification on a new really tar free downdraft gasifier - Pedroso, Daniel Travieso; Aiello, Ramon Cala; Conti, Leonetto; Mascia, Stefano (Revista Ciências Exatas, 2008)
One of the major obstacles for the application of biomass gasification systems is the high tar content of the producer gas that prevents the use in engines, turbines or fuel cells without further gas cleaning. In this work, features of a novel tar free gasifier are described. Producer gas, containing 2 mg/Nm3 of tar and dust was obtained. This gas can be used directly to fuel cycle Otto engines to produce electricity and heat. Biomass was converted in producer gas with up to 78% efficiency. Typically from 1.3 kg of woody biomass in dry base, 1 kWhe and up to 2 kWht can be obtained. Operations and maintenance are very simple and can be carried out by non-skilled operators.